Structure of muscle strength among professional classical female dancers - Dworak, L. B.; Gorwa, J.; Kabaciñski, J.; Mczyñski, J.; Murawa, M. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The work characterizes in detail the level of static torques in classical ballet female dancers, in comparison to their peers, students of physiotherapy at the University of Medical Sciences. The analysis of torques consisted in evaluation of 13 functional muscle groups (11 groups of left and right extremities and 2 of the trunk). Apart from few exceptions, the tested dancers were stronger, however the difference was not always statistically significant.